TRANSFORMATION OF FORM, FUNCTION, AND MEANING SACRED SPACE OF GEDHONG JENE KRATON YOGYAKARTA - Denok Estu Kuncoro; Purwanita Setijanti; Didit Novianto (Jurnal Arsitektur ARCADE, 2024)
Abstract: The fusion of cultural and social accumulations is capable of creating architectural works with specific functions and meanings. In Indonesia, Kraton Yogyakarta, which continues to uphold its role as a traditional palace. However, the transition from an absolute monarchy to a republic, has led the transformation in form, functions, and meanings of spaces in the kraton. Spaces previously used by the king now serve different functions, sacred spaces are repurposed for more general purposes. Gedhong Jene, one of these spaces, responds to these changes, evidencing an adaptation from a space exclusively for the king to a more inclusive functionThis research aims to conduct an analysis of the transformation of Gedhong Jene as a reflection of the dynamic political and socio-cultural developments within the Kraton Yogyakarta. Used qualitative approaches, the study will explore the change in function and meaning of Gedhong Jene's space, considering both its architectural and non-architectural elements. Data gathered from observations, interviews, and archival documents will be analyzed using descriptive criticism.The research findings revealed significant changes in Gedhong Jene, particularly in its static and dynamic aspects. However, the building exhibited more complex functionality following these alterations. Keyword: Transformation of Sacred Space, Gedhong Jene, Kraton YogyakartaAbstrak: Perpaduan akumulasi budaya dan sosial mampu menghasilkan karya arsitektur yang memiliki fungsi dan makna tertentu. Di Indonesia, salah satunya adalah Kraton Yogyakarta yang hingga saat ini masih memegang peranannya sebagai kerajaan tradisional. Namun, seiring adanya perubahan sistem pemerintahan absolut ke sistem republik, hal ini berdampak pada perubahan bentuk dan pergeseran fungsi dan makna ruang di dalam kraton. Ruang-ruang yang sebelumnya digunakan hanya untuk keperluan raja kini memiliki fungsi yang berbeda, ruang-ruang yang dianggap sakral difungsikan untuk tujuan yang lebih umum. Gedhong Jene, salah satu ruang yang merespons perubahan tersebut. Bangunan ini menjadi bukti adanya adaptasi dari ruang sakral yang hanya digunakan untuk raja menjadi lebih inklusif. Penelitian ini bertujuan untuk melakukan analisis mendalam terhadap perubahan ruang Gedhong Jene sebagai cerminan dari perkembangan dinamika politik dan sosial budaya yang terjadi di Kraton Yogyakarta. Penelitian kualitatif digunakan untuk mengeksplorasi perubahan bentuk, fungsi, dan makna ruang Gedhong Jene dilihat dari elemen-elemen arsitektur maupun non-arsitekturnya. Data didapatkan dari observasi, wawancara, serta penggunaan dokumen arsip kraton yang nantinya akan dianalisis menggunakan descriptive criticism. Hasil dari penelitian ini menunjukkan adanya perubahan yang signifikan pada Gedhong Jene, terutama dalam aspek statis dan dinamisnya. Namun, bangunan menunjukkan fungsionalitas yang lebih kompleks setelah adanya perubahan.Kata Kunci: Transformasi Ruang Sakral, Gedhong Jene, Kraton Yogyakarta